MiR-590-3p suppresses cellular migration and clonogenicity and epithelial to mesenchymal transition in the HepG2 cell line by targeting MDM2 and SETD7 - Youssef, Alaa (AUC Knowledge Fountain, 2020)
MiRNAs signature is dysregulated in various types of cancer, and several miRNAs have a dual regulatory role either as tumor suppressors or oncogenes depending on the tissue context. MiR-590-3p has been previously identified to regulate different cancers, yet its role in hepatocellular carcinoma (HCC) is still elusive with contradictory findings. In our study, the expression levels of miR-590-3p, as well as its function in HCC, were examined in two different HCC cell lines: HepG2 and SNU449 that represent an early and advanced stage of HCC, respectively. Real-time Polymerase Chain Reaction analysis revealed that miR-590-3p is downregulated in HCC and its levels are more decreased as HCC advances to a more malignant state. Functional analysis was performed by ectopically overexpressing and inhibiting miR-590-3p using miRNA mimics and inhibitors in HepG2 and SNU449 cells. Using Condition-Specific miRNA Targets (CSmiRTar) database to predict mir-590-3p targets, MDM2, and SETD7 were identified. A validation of the two targets was demonstrated through an established negative correlation between their mRNA levels and miR-590-3p level in both cell lines. Further validation of the two genes was represented in the decreased mRNA expression upon overexpressing miR-590-3p. Furthermore, miR-590-3p overexpression was able to decrease epithelial to mesenchymal transition by directly reducing the mRNA level of the mesenchymal marker N-cadherin. MiR-590-3p also suppressed cell migration and reduced clonogenicity in the HepG2 cell line. Interestingly, real-time PCR and western blotting analyses revealed stabilization of p53 mRNA and protein levels as a result of miR-590-3p transfection in both HepG2 and SNU449 cells, which could be mainly attributed to a unique dual regulation event from both MDM2 and SETD7 on p53 that eventually led to a stable p53 expression. Finally, our results confirm a tumor-suppressive role of miR-590-3p in HCC through the regulation of both MDM2 and SETD7.